Development of vacuum dehydrated powdered ginger (Zingiber officinale roscoe var. Hawaiian) - Pardo, Lorna V.; De Leon, Sonia Y. (1974.)
Powdered ginger was developed from fresh Hawaiian ginger by vacuum oven dehydration. Variables studied were two types of raw materials, freshly ground and freshly sliced, and the temperatures of dehydration, 100°F, 130°F and 170°F. Peeling treatments (lye peeling, steam blanching and boiling water blanching) were conducted to determine their effect on essential oil content of the finished products relative to flavor and aroma retention of ginger. Subjective and ibjective tests favored the sliced samples dehydrated at 170°F for 2.83 hours. Relative to the peeling treatments done, the blanched samples have higher essential oil retention and panel scores than the lye treated samples. Steam and boiling water blanching did not improve the peel serapeability and the color of the outermost layer of the pulp turned to brown. The peeling treatments gave slightly inferior products than the control. Results of the two phases favored the sliced sample dried at 170°F without peeling treatment. The resultant powder has 1.20ml essential oil per 100 grams of samples and 4.8% moisture content.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Ginger